2022
DOI: 10.11604/pamj.2022.43.38.31329
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 loss of taste and smell: potential psychological repercussions

Abstract: The novel coronavirus (COVID-19) has become a cause for global concern. Apart from a multitude of symptoms, the virus is known for its ability to cause loss of taste and smell that can be irreversible in a few cases. In fact, even after recovery, post-covid syndrome can still lead to devastating outcomes, specifically with reference to loss of smell and taste. A number of mechanisms that have been postulated include receptor-mediated uptake, increased inflammation, transneuronal migration, and direct damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…This study investigated the experiences and coping methods of patients who experienced long-term loss of smell after COVID-19. 30 The main points that stand out in the descriptive characteristics of the participants in the study can be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the experiences and coping methods of patients who experienced long-term loss of smell after COVID-19. 30 The main points that stand out in the descriptive characteristics of the participants in the study can be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%
“…22 Smell and taste disturbances have also been shown to have significant psychosocial implications on patients’ quality of life and well-being, putting patients at higher risk of anxiety and depression. 13,16,17 Previous literature has demonstrated that worse olfactory function correlates with worse olfactory-specific quality of life. 15 Patients report the inability to enjoy food, maintain their appetite and nutritional status, participate in social gatherings, and maintain personal hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…15 Patients report the inability to enjoy food, maintain their appetite and nutritional status, participate in social gatherings, and maintain personal hygiene. 13 Additionally, patients with diminished senses face safety concerns such as the inability to detect smoke, fires, or gas leaks, and can also impact professional careers for chefs, firefighters, and perfumers for example. 13,23,24 Without documentation and record-keeping of smell or taste dysfunction, new providers may not be aware of the impact of untreated disease on quality of life, nutrition, and physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations